Composition and Member Qualifications of Audit Committee and Audit Fees: The Different Moderating Effects of Ownership Structure - Lee, Sang Cheol; Yoon, Jongchul; Yoo, Jungmin; Lee, Yunkeun (Korean Accounting Review, 2024)
Using 1,411 non-financial firm-year observations from companies listed on the Korean Composite Stock Price Index (KOSPI) between 2001 and 2012, we analyze various characteristics related to audit committee composition and member qualifications for Korean companies. We classify these characteristics conceptually and aggregate them into a comprehensive measure. We then empirically test the effects of these categorized characteristics and the comprehensive measure on audit fees. Additionally, we investigate how the impact of these characteristics and the comprehensive measure on audit fees varies with different ownership structure characteristics in Korea. Our key findings are as follows: First, the perceived independence and expertise of audit committees have a significantly positive impact on audit fees. Conversely, impaired substantive independence of audit committees negatively impacts audit fees. Notably, perceived independence among the conceptually classified characteristics has the greatest impact on audit fees, underscoring its crucial role in determining audit fees. Second, the comprehensive measure of audit committee composition and member qualifications significantly increases external audit fees. Third, the influence of audit committee independence, expertise, and the comprehensive measure on audit fees is enhanced with higher foreign and institutional investor ownership. In contrast, this influence decreases as the ownership of the largest shareholder increases.
Keywords: audit committee; audit fees; composition; comprehensive measure; member qualification; ownership structure